2012
DOI: 10.1002/bse.1740
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium‐Sized Enterprises and Sustainability: Managers' Values and Engagement with Environmental and Climate Change Issues

Abstract: This article reports on an in‐depth, qualitative study into the pro‐environmental engagement of small businesses in the east of England, with respect to climate change in particular. Managers of environmentally pro‐active small businesses were asked about the pro‐environmental measures they had implemented in their firms, their motivations for doing so, and their understanding of climate change. The managers in this study had a relatively good understanding of environmental issues in general and climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
341
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(359 citation statements)
references
References 53 publications
14
341
2
2
Order By: Relevance
“…[T]he massive changes occurring in the natural environment, and a growing attention to, and understanding of, these changes redefine the institutional and natural environment of firms and their markets, thus generating additional opportunities in the marketplace (Cohen and Winn, 2007, p. 44). However, while these commercial priorities play a decisive role in this developing economy context, the study has also revealed other important drivers, including the sustainability-driven values of SME owners and managers (Hamann et al, 2017;Hammann et al, 2009;Testa et al, 2016;Williams and Schaefer, 2013). Crucially, it has shown how both value-based motivations for adopting pro-environmental practices, and a greater awareness of their potential commercial benefits, have largely been mediated by the educational and awareness-raising activities of intermediary organisations, such as CPC and CPI (Ortolano et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[T]he massive changes occurring in the natural environment, and a growing attention to, and understanding of, these changes redefine the institutional and natural environment of firms and their markets, thus generating additional opportunities in the marketplace (Cohen and Winn, 2007, p. 44). However, while these commercial priorities play a decisive role in this developing economy context, the study has also revealed other important drivers, including the sustainability-driven values of SME owners and managers (Hamann et al, 2017;Hammann et al, 2009;Testa et al, 2016;Williams and Schaefer, 2013). Crucially, it has shown how both value-based motivations for adopting pro-environmental practices, and a greater awareness of their potential commercial benefits, have largely been mediated by the educational and awareness-raising activities of intermediary organisations, such as CPC and CPI (Ortolano et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…There is evidence that, in some SMEs, the environmental values of owner-mangers have induced the adoption of sustainable practices (e.g. Battisti and Perry, 2011;Hamann et al, 2017;Hammann et al, 2009;Hsu and Cheng, 2012;Testa et al, 2016;Williams and Schaefer, 2013). However, though in a minority, some studies still suggest that the environmental attitudes of owners might not serve as an effective predictor of the environmental behaviour in smaller firms (Schaper, 2002).…”
Section: Entrepreneurs' Moral Valuesmentioning
confidence: 99%
“…Given the scant nature and the limited scope of research on managerial perspectives on menu design as a facilitator of more responsible consumer choice in restaurants, and due to the difficulties in recruiting willing industry professionals as highlighted by previous studies (Poulston and Yiu 2010;Williams and Schaefer 2013), this project chose to employ an interpretive, qualitative method of primary data collection and analysis (semi-structured interviews). Qualitative inquiry is exploratory by nature which limits the empirical generalisability of its findings and yet it enables in-depth evaluation and conceptualisation of people's opinions whose outcome can subsequently be tested in quantitative analysis (Braun and Clark 2006).…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics aid SMEs to adopt CSR practices, as most of the decisions are made by the owners of SMEs. Entrepreneurs managing SMEs make decisions, initiate and implement CSR activities [27,28], which in turn contribute to the competitiveness and growth of the firm [29,30]. Furthermore, the focus of CSR practices in SMEs is often with the immediate stakeholders, employees, followed by the community, and the least practiced aspect of CSR is environment related [31,32].…”
Section: Csr In Smesmentioning
confidence: 99%